Clinical and pathological features of mammary tumors in female dogs (Canis familiaris) - Caldas, Saulo Andrade; Miranda, Ileana Costa; Brito, Marilene de Farias; Nogueira, Vivian de Assunção; Cid, Gabriela de Carvalho; Costa, Samay Zillmann Rocha; França, Ticiana do Nascimento; Pinto, Luiz Figueira (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Caldas S.A., Miranda I.C., Brito M.F., Nogueira V.A., Cid G.C., Costa S.Z.R., França T.N. & Pinto L.F. [Clinical and pathological features of mammary tumors in female dogs (Canis familiaris).] Aspectos clínico-patológicos das neoplasias mamárias em cadelas (Canis familiairs). Revista Brasileira de Medicina Veterinária, 38(Supl.2):81-85, 2016. Departamento de Medicina e Cirurgia Veterinária, Universidade Federal Rural do Rio de Janeiro, BR-465 Km 7, Seropédica, RJ 23890-000, Brasil. E-mail: saulocaldas@hotmail.com Mammary tumors are one of the most common neoplasms in female dogs, and histopathological diagnosis is an important method to support clinical and surgical therapies. This study aimed to describe the clinical and pathological aspects of female dogs with mammary tumors treated at the Veterinary Hospital of Federal Rural University of Rio de Janeiro. A total of 141 patients were evaluated between March 2014 and December 2015, and data about age, breed, body condition and reproductive history, as well as the number of nodules, size, location, stage of development, duration and histopathological diagnosis of the tumors were analyzed. The highest incidence of mammary tumors occurred in dogs between 8 and 14 years. Most tumors were in stage III of development, based on the TNM system. Histopathology revealed 56% of malignancies compared to 44% of benign tumors. Surgical cure was achieved in 93.61%, which is considered an excellent result, given the advanced age and tumoral stage of most animals.